Physics Education and Sustainable Development: A Study of Energy in a Glocal Perspective in an Angolan Initial Teacher Education School - Malavoloneque, Gilberto; Costa, Nilza (Frontiers in Education, 2022)
Education is a key element to address Sustainable Development Golas/SDG. This is particularly relevant in developing countries (e.g. Angola) where politicians signed agendas (2030&2063 but their commitment is far from expected. One issue of these agendas is the sustainable production&use of energy, where Angola faces a serious situation given the strong petroleum dependence&the weak use of alternative energy resources. Despite recent national policies, Physics Education in Angola is characterized by traditional practices. Therefore, this study questions: how electric energy may be taught in a Physics course of an Initial Teacher Education Programme to develop teachers educators' conceptions&practices. Empirically, the study included a case study/CS in a Physics Course for future Physics teachers in an Angolan School&an exploratory study/ES one year later. Data collection used a variety of techniques&instruments in the CS (e.g. documental analysis; questionnaire; Physics Teachers documents produced in an intervention action where a didactic sequence about energy was negotiated)&in the ES a focus group with Physics Teachers involved in the CS. Data was treated by statistics&content analysis. Although the results cannot be statistically generalized, they suggest that: with the traditional approach, the future teachers learnt academic concepts but do not know/nor see the importance of local energy resources&do not value their role as active citizens; the teachers educators agreed with the didactic sequence to improve their teaching; one year later, teachers refer to have changed their practices. Recommendations pointed to promote teacher professional development to contribute to the SDG&educational research as a collaborative process to support&sustain new practices.